Reality therapy in groups - Wubbolding, Robert; Microtraining Associates; Association for Specialist in Group Work (North Amherst, MA : Distributed by Microtraining Associates)
Explains on control theory as it applies to group counseling, the practical application of reality therapy on environment and procedures, the role play and debriefing of role play
Title from title screen
Keywords: Reality therapy; Counseling; Psychotherapy